Isocitrate Dehydrogenase 1 (IDH1) Mutation in Breast Adenocarcinoma Is Associated With Elevated Levels of Serum and Urine 2-Hydroxyglutarate. (23rd April 2014) - Fathi, Amir T.; Sadrzadeh, Hossein; Comander, Amy H.; Higgins, Michaela J.; Bardia, Aditya; Perry, Ashley; Burke, Meghan; Silver, Regina; Matulis, Christina R.; Straley, Kimberly S.; Yen, Katharine E.; Agresta, Sam; et al.
Abstract: Mutations in the IDH1 and IDH2 (isocitrate dehydrogenase) genes have been discovered across a range of solid-organ and hematologic malignancies, including acute myeloid leukemia, glioma, chondrosarcoma, and cholangiocarcinoma. An intriguing aspect of IDH -mutant tumors is the aberrant production and accumulation of the oncometabolite 2-hydroxyglutarate (2-HG), which may play a pivotal oncogenic role in these malignancies. We describe the first reported case of an IDH1 p.R132L mutation in a patient with hormone receptor-positive (HR+) breast adenocarcinoma. This patient was initially treated for locally advanced disease, but then suffered a relapse and metastasis, at which point an IDH1-R132 mutation was discovered in an affected lymph node. The mutation was subsequently found in the primary tumor tissue and all metastatic sites, but not in an uninvolved lymph node. In addition, the patient's serum and urine displayed marked elevations in the concentration of 2-HG, significantly higher than that measured in six other patients with metastatic HR+ breast carcinoma whose tumors were found to harbor wild-type IDH1. In summary, IDH1 mutations may impact a rare subgroup of patients with breast adenocarcinoma. This may suggest future avenues for disease monitoring through noninvasive measurement of 2-HG, as well as for the development and study of targeted therapies against the aberrant IDH1 enzyme. Abstract : The authors describe the case of one patient with hormone receptor-positive breast adenocarcinoma with a somatically acquired IDH1 (isocitrate dehydrogenase 1) p.R132L mutation. The patient's serum and urine displayed marked elevations in the concentration of the oncometabolite 2-hydroxyglutarate (2-HG). These findings may suggest future avenues for disease monitoring through noninvasive measurement of 2-HG, as well as for the development and study of targeted therapies against the aberrant IDH1 enzyme.